Positive outcomes between crop diversity and agricultural employment worldwide - Garibaldi, Lucas Alejandro (2019)
Fil: Garibaldi, Lucas Alejandro. Universidad Nacional de Río Negro. Instituto de Investigaciones en Recursos Naturales, Agroecología y Desarrollo Rural; Argentina.